Estudio de propuestas alternativas en la enseñanza de la termodinámica básica - Martínez, J. M.; Pérez, B. A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
We report in this work a research on an approach to Basic Thermodynamics teaching at secondary level. The results of four grups of students in different cities are discussed from qualitative and global quantitative perspectives in a complementary way. We suggest, in the light of the real implementation of that curricular proposal, some didactic recommendations for better adequacy to different contexts.